Pengaruh Harga Jual Minyak Goreng Bimoli terhadap Keputusan Pembelian di Toko Andika Distrik Mega Kabupaten Sorong - Edward Clan; Lili Sarce Joi Sapari; Melkior Paa (Departement of Mathematics Education, 2023)
The problems faced by the community or consumers in the mega district are: the reach faced by the community in the mega district, the obstacle is that it is far from the mega district to Sorong district to shop in Sorong district so that the community or consumers can make decisions to be able to choose Andika shop is an alternative to be able to shop for Bimoli cooking oil at Andika shop, because Andika shop is very close in the Mega District and the reach of the public or consumers to be able to shop at Andika shop is very close so that it can ease the economy of the people or consumers in the Mega District, Sorong Regency. The analysis technique used is simple linear regression. The results of the tests conducted in this study stated that there was a positive influence between the selling price of bimoli oil and the purchase decision of 0.744 with a significance level of 0.000, less than 0.005. The relationship between the selling price of bimoli oil and the purchase decision at the Andika Store, Mega District, Sorong Regency is based on a correlation coefficient analysis (R) of 0.785 and based on testing the coefficient of determination (R2) of 0.616 or 61.6% and 28.5% is influenced by other factors such as promotion.